Strategies for Successful Customer Retention in Multinational Bank with Reference to Standard Chartered Bank - Debajani Sahoo, Dr.; Sureshkumar, S. (Journal of Contemporary Research in Management (JCRM), 2013)
In banks the concept of customer retention is held in high esteem but most of the bankers are still not sticking to that. Customer retention is the buzzword for all times rather than the concepts as benchmarking or best practices, more than process reengineering or quality management. ToÂ meet the threat of competition and retain customer base, banks now looking at business process management (BPM) to increase returns on investment, improve customer relationship management (CRM) and employee productivity. This paper helps to know the different strategies to be followed by Standard Chartered Bank (SCB) bank to retain their existing customers. The arrival of foreign and private banks with their superior state-of-the-art technology-based services pushed Indian BanksÂ also to follow suit by going in for the latest technologies, the study has been carried out to find out what can be further done. Statistical tool like Simple average and one way ANOVA methods are used to meet theÂ objectives.